Dopamine partial agonists and prodopaminergic drugs for schizophrenia: Systematic review and meta-analysis of randomized controlled trials. (April 2022) - Osugo, Martin; Whitehurst, Thomas; Shatalina, Ekaterina; Townsend, Leigh; O'Brien, Oisin; Mak, Tsz Lun Allenis; McCutcheon, Robert; Howes, Oliver
Abstract: Dopaminergic dysfunction is thought to be central to schizophrenia symptomatology. Previous meta-analyses of prodopaminergic drugs in schizophrenia have important limitations, and also did not include dopamine D2/D3 partial agonists. We investigated the effect of medications which increase dopamine signalling on schizophrenia symptoms by meta-analysing double-blind, placebo-controlled RCTs. 59 RCTs were included: 29 of prodopaminergic treatments, 30 of partial agonists. Partial agonists were significantly superior to placebo against positive (SMD=−0.33, p = 1.2 ×10 -17 ), negative (SMD=−0.29, p = 2.2 × 10- 31 ) and total symptoms (SMD =−0.39, p = 1.7 × 10 -30 ) in schizophrenia. There were no significant differences between pooled pro-dopaminergic drugs and placebo in any symptom domain. In subgroup analysis of five studies where patients were selected for negative symptom severity, ar/modafinil was superior to placebo against negative symptoms (SMD=−0.34, p = 0.037). These data favour the clinical use of partial agonists for negative symptoms in schizophrenia, with clinically meaningful effect sizes. Our findings also suggest a benefit for ar/modafinil in patients with predominant negative symptoms. Future trials of other prodopaminergic therapies and dopamine partial agonists in patients with predominant negative symptoms are warranted. Highlights: Dopaminergic dysfunction is thought to be central to schizophrenia symptomatology. This meta-analysis synthesises results from 59 double-blind RCTs of drugs which increase dopamine signalling in schizophrenia. Dopamine partial agonists are superior to placebo in the treatment of positive, negative and total symptoms in schizophrenia. Pooled prodopaminergic drugs are not significantly different from placebo against any symptom domain. Adjunctive ar/modafinil is superior to placebo against negative symptoms in patients selected for negative symptom severity.